Exploring the perceptions of young people in care and care leavers of their health needs - Julie Ridley; Steven McCluskey (Scottish Journal of Residential Child Care)
The health of young people in public care has received increased attention at a political and practice level in recent years. The introduction of national care standards (Scottish Executive 2002) in areas relating to health by the newly formed Scottish Commission for the Regulation of Care ('the Care Commission') is a welcome development. These standards, it is hoped, will significantly contribute to the improvement of young people’s health whilst being looked after away from home.